Effects of Increasing Dietary Alpha-Linolenic Acids on Nursery Pig Growth Performance and Response to Immune Challenge - Jenna J. Bromm; Mike D. Tokach; Jason C. Woodworth; Robert D. Goodband; Joel M DeRouchey; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 350 weanling pigs (Line 241 × 600, DNA; initially 12.7 ± 0.1 lb BW) were used in a 41-d study to evaluate growth performance and immune response of nursery pigs fed diets containing increasing alpha-linolenic acids using O3 Trial Feed, a source of omega-3 fatty acids. At weaning, pigs were randomly assigned to 1 of 5 dietary treatments with 5 pigs per pen and 14 replications per treatment. Treatments were arranged in a completely randomized design. Dietary treatments consisted of increasing levels (0, 1, 2, 3, or 4%) of O3 Trial Feed. This resulted in omega-6:3 fatty acid ratios ranging from approximately 25:1 to 4:1. Treatment diets were fed in 3 phases with phase 1 fed from d 0 to 13, phase 2 from d 13 to 22, and phase 3 from d 22 to 41. On d 25, two pigs per pen were injected with 20 μg ofEschrichia coli (E. coli) lipopolysaccharide (LPS) per kg BW and one pig per pen was injected with 2 mL of saline to serve as a control. Body temperature was recorded from the 3 pigs per pen prior to the injection (hour 0) and 2, 4, 6, and 12 h after injection. On d 25 a blood sample was collected 4 h post injection from pigs injected with the LPS challenge to determine IL-1β levels in the serum. For overall growth performance, there were no differences observed in ADG, ADFI, or F/G. Temperature increased at 2 h post LPS injection, then decreased as time from the LPS injection increased, but dietary treatment did not influence change in body temperature or IL-1β. These results indicate dietary alpha-linolenic acid levels did not influence growth performance or immune response to a LPS challenge.
Keywords: Omega-3; nursery pigs; LPS; O3 Trial Feed